The influence of company size and profitability on carbon accounting information disclosure: evidence from the shanghai a-share heavily polluting industries - Yi, Hua Luo; Thien, Sang Lim; Jainurin Justine @ Abdul Aziz; Xiaobin Luo (Penerbit Universiti Malaysia Sabah, 2024)
In this study, the relationship among firm size, profitability, and carbon accounting information disclosure (CAID) of 131 highly polluting Shanghai A-share listed companies was analysed using a multivariate regression approach based on the stakeholder theory. The results revealed that larger and more profitable companies were more transparent in disclosing carbon accounting information, which aligned with stakeholder expectations. This study enhanced the comprehension of the interplay between company characteristics and CAID dynamics and emphasised its pivotal role in fostering sustainability and transparency. The insights are valuable for policymakers, industry experts, and stakeholders and guide environmentally responsible business practices.